PENGARUH PREFERENSI DAN HARGA TERHADAP SIKAP DAN IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN INDOMIE RASA CABE IJO DI SEMARANG - Yanudhita Larasati, Claresta; Widiyanto, Ibnu (Diponegoro Journal of Management, 2013)
In Indonesian instant noodle market is lucrative. Indonesian people's dependence on fast food noodle is quite large. In this case also sparked instant noodle companies to compete in order to gain market share by offering products that meet the needs of consumers, because of the competition, the Indomie sales decline. To increase sales, Indomie do product development by releasing new products that Indomie Rasa CabeIjo. This study aimed to analyze the influence of preferences and price on customer attitudes and customer loyalty products Indomie Rasa CabeIjo in Semarang         This research uses multiple linear regression analysis using SPSS. The population is the city of Semarang who like to eat Indomie taste green chillies. While the sample is used as many as 100 people with non-random sampling method is to take samples at several stores and a minimarket in Semarang.The results showed that the preferences and price positive and significant impact on customer attitudes and customer attitudes positive and significant effect on customer loyalty products Indomie Rasa Cabe Ijo in Semarang. In the model 1, giving preference to the most influence customer attitudes of 0.648. In model 2, giving preference to the most influence customer loyalty of  Indomie Rasa Cabe Ijo product in Semarang at 0.341.